Effect of dehydrated molasses with minerals and urea in pineapple straw silage. - Rodríguez-Chacón, Sofía; López-Herrera, Michael; WingChing-Jones, Rodolfo; Rojas-Bourillón, Augusto (Agronomía Mesoamericana, 2014)
The objective of this study was to determine the effect of urea and dehydrated molasses with minerals (DMM) on pineapple straw silage. The preparation of the straw was done from April to June, of 2010, and involved using the micro silage technique in 1kg bags. The treatments were performed using four levels of urea (0, 0.5, 1, 1.5% w/w), four DMM levels (0, 0.2, 0.4, 0.6% w/w) and a single concentration of bacterial inoculum (1 l/t) for all treatments. Results showed that DMM significantly increases the variables of pH (2.84 to 8.23) and ash (8.1 to 16.1% DM), but reduces in vitro digestibility (67.3 to 54.0%). Urea also affected significantly and proportionally pH, buffer capacity, ammonia nitrogen (NH3-TN) (3,87 to 7.10% NH3/TN) and crude protein (CP) (8.2 to 18.3% DM). Nonetheless these additives had no effect on dry matter and fiber content in ensiled materials. We conclude that the content of non-fibrous carbohydrates (NFC) rises when the level of DDM in silage is increased while urea has the opposite effect.